Human Skeletal Stem Cell Response to Multiscale Topography Induced by Large Area Electron Beam Irradiation Surface Treatment - Goriainov, Vitali; Cook, Richard B.; Murray, James W.; Walker, John C.; Dunlop, Douglas G.; Clare, Adam T.; Oreffo, Richard O. C. (Frontiers in Bioengineering and Biotechnology, 2018)
The healthcare socio-economic environment is irreversibly changing as a consequence of an increasing ageing population, consequent functional impairment and patient quality of life expectations. The increasing complexity of ensuing clinical scenarios compels a critical search for novel musculoskeletal regenerative and replacement strategies. While joint arthroplasty is a highly effective treatment for arthritis and osteoporosis, further innovation and refinement of uncemented implants are essential in order to improve implant integration and reduce implant revision rate. This is critical given financial restraints and the drive to improve cost-effectiveness and quality of life outcomes. Multi-scale modulation of implant surfaces, offers an innovative approach to enhancement in implant performance. In the current study, we have examined the potential of large area electron beam melting to alter the surface nanotopography in titanium alloy (Ti6Al4V). We evaluated the in vitro osteogenic response of human skeletal stem cells to the resultant nanotopography, providing evidence of the relationship between the biological response, particularly Collagen type I and Osteocalcin gene activation, and surface nanoroughness. The current studies demonstrate osteogenic gene induction and morphological cell changes to be significantly enhanced on a topography Ra of approximately 40 nm with clinical implications therein for implant surface treatment and generation.